Impact of Personal Biases and Organizational Politics on Performance Appraisal Systems- A Case Study of the Service Sector of Pakistan - Prof. Dr. Muhammad Shoukat Malik; Hiba Sagheer (Journal of Management Practices, Humanities and Social Sciences, 2022)
The performance of the appraisal system is investigated in this article concerning to personal bias and Organizational Politics (OP). This article focuses on the problems with the evaluation processes that are impacted by bias, internal politics, and incorrect assessments of employees' performance. Data collection using the practical sampling technique. Additionally selected for this article are five public service organizations: WAPDA, PIA, MDA, NADRA, and WASA. Twenty managers and 250 middle-level employees make up the sample size for the analysis. To evaluate the hypothesis, regression analysis technique was used, along with Process modeling for mediation and moderation. The research in this paper demonstrates the considerable effects of individual prejudice, workplace politics, and performance evaluation systems. Previous literature is limited in examining the relationship that such biasness and political exploitation of the organization contributes to employee discontent, impacting the company's norms and Employee Perception (EP) that they are not correctly paying (Ayegi, 2019 & Guo 2019). To contribute to the formation of public companies, managers must foster and value a positive culture. Organizational Culture (OC) does not significantly affect performance evaluation methods, but the moderation and mediation of the variables produced significant results. Employees form the strong impression that the organization has a biased culture. Long-term commendation must make employees feel valued by their bosses to be effective in positive attitudes.